Estimates of Earthquake with Markov models in the East Anatolian Fault Zone - Doğaner, Adem; Çalık, Sinan (My University, 2013)
Stochastic methods are often used for estimates of future for environmental events realized. Markov chains are one of these methods. Markov chains can applied to estimates of the earthquake but it provides only information about a single parameter. In this article, epicenter of may occurring earthquake were estimated on East Anatolian Fault Zone. Epicenter parameter and times of seismic inactivity were associated for estimates of earthquake. Probabilities were provided by Hidden Markov Model with forwards algorithm and these probabilities were converted to state sequence. Transition probabilities of this sequence were examined with Discrete Time Markov Chains. As a result new earthquake were expected in 4th state (Sincik- Lake Hazar ) with 0.73 probabilities. Results and method were discussed.

Stokastik yöntemler sıklıkla geleceğe yönelik çevresel olayların gerçekleşme tahminleri için kullanılabilmektedir. Markov zincirleri bu yöntemlerden biridir. Markov zincirleri deprem tahminlerinde uygulanabilmektedir, fakat bu yöntem sadece bir parametreye ilişkin bilgi sağlamaktadır. Bu çalışmada, Doğu Anadolu Fay Zonu üzerinde gerçekleşecek depremin dış merkezi tahmin edilmiştir. Olasılıklar, saklı Markov modeli ve ileri algoritması ile elde edilmiştir. Bu olasılıklar durum zincirine dönüştürülmüştür. Geçiş olasılıkları, kesikli parametreli Markov zincirleri ile incelenmiştir. Sonuç olarak yeni deprem 0.73 olasılıkla 4.durum olarak belirtilen Sincik- Hazar Gölü segmenti üzerinde gerçekleşebileceği tahmin edilmiştir. Sonuçlar ve metot tartışılmıştır.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hidden Markov model; Epicenter; East Anatolian Fault Zone; Saklı Markov modeli; Dış merkez; Doğu Anadolu Fay Zonu